Personal profiles: enhancing social interaction in learning networks. (19th January 2011) - Berlanga, Adriana J.; Bitter-Rijpkema, Marlies; Brouns, Francis; Sloep, Peter B.; , Sibren Fetter
Nowadays, we can witness a surge of online profiling sites; in them people make their profile available to others with the intention to share it and get in touch with others, find old friends, classmates or colleagues, or look for new opportunities. Given their capacity to encourage members to be connected with other members and their growing popularity, we hold that some lessons can be learned from such profiling sites. In this paper's initial exploration, we analyse some of the most popular profiling sites to spot indications on profile composition and the affordances they use to encourage people to interact and to establish connections with other members. Based on this we discuss the importance of personal profiles depicting the characteristics and support mechanisms needed to enhance social interaction in learning networks. We also present results of a pilot survey of actual use and perception of user profile sites, and comment on the current views and findings about this topic in the Web-Based Communities Conference of 2008.